The Legal Nature of Civil Responsibility from Plastic Surgery - Kab, Amel; Lallouche, Samira (Journal of Legal Studies and Researches, 2022)
Plastic surgery is one of the most important topics that deserve legal study due to its wide spread and the difficulty of determining its legal nature, which raises several problems in terms of the nature of the civil responsibility of the plastic surgeon and its characteristic son of the responsibility of the ordinary surgeon, The legislation, it was more stringent regarding the responsibility of the doctor in plastic surgery, unlike in other surgeries. The importance of plastic surgery is shown through its types.